CFTR p.Arg117His associated with CBAVD and other CFTR-related disorders. Issue 4 (1st February 2013) - Thauvin-Robinet, Christel; Munck, Anne; Huet, Frédéric; de Becdelièvre, Alix; Jimenez, Clément; Lalau, Guy; Gautier, Elodie; Rollet, Jacques; Flori, Jean; Nové-Josserand, Raphaëlle; Soufir, Jean-Claude; Haloun, Alain; et al.
Abstract : Background: The high frequency of the cystic fibrosis (CF) transmembrane conductance regulator ( CFTR ) gene mutation p.Arg117His in patients with congenital bilateral absence of the vas deferens (CBAVD) and in newborns screened for CF has created a dilemma. Methods: Phenotypic and genotypic data were retrospectively collected in 179 non-newborn French individuals carrying p.Arg117His and a second CFTR mutation referred for symptoms or family history, by all French molecular genetics laboratories, referring physicians, CF care centres and infertility clinics. Results: 97% of the patients had the intronic T7 normal variant in cis with p.Arg117His. 89% patients were male, with CBAVD being the reason for referral in 76%. In 166/179 patients with available detailed clinical features, final diagnoses were: four late-onset marked pulmonary disease, 83 isolated CBAVD, 67 other CFTR-related phenotypes, including 44 CBAVD with pulmonary and/or pancreatic symptoms and 12 asymptomatic cases. Respiratory symptoms were observed in 30% of the patients, but the overall phenotype was mild. No correlation was observed between sweat chloride concentrations and disease severity. Five couples at risk of CF offspring were identified and four benefited from prenatal or preimplantation genetic diagnoses (PND or PGD). Eight children were born, including four who were compound heterozygous for p.Arg117His and one with a severe CF mutation. Conclusions: Patients with CBAVD carrying p.Arg117His and a severe CF mutation should benefit from a clinical evaluation and follow-up. Depending on the CBAVD patients' genotype, a CFTR analysis should be considered in their partners in order to identify CF carrier couples and offer PND or PGD.